Parenting self efficacy ayah dan ibu pada pasangan suami istri yang menikah dini - Inges Dwi Pangestu (Cognicia, 2020)
Early married teenage couples have an impact on proper parenting in children. In order to be a good parent and can provide the right parenting for the child, then it takes high parenting self efficacy on parents. Parenting Self Efficacy is a belief in the competence that is held in organizing and executing a series of tasks on parenting. The purpose of this research is to describe parenting self efficacy father and mother on married couples in early marriage, the design of this research is quantitative descriptive, this study gives a detailed picture of an event based on the data that has been collected in the form of numbers, then analyzed and interpreted. The subject of this study is 30 couples who marry early with the age range of 17-20 years and have children aged 0-3 years. The sampling technique used is snowball sampling. The study used the Father Self Efficacy scale (FSES) scale for the Father And the maternal self efficacy Questioner (MSQ) scale for mothers. The results of this study were analyzed using SPSS. 21 for Windows using a descriptive test technique. The results of this study showed that the teenage father who has a high parenting self efficacy that is 63% later on a teenage mother who has a high parenting self efficacy of 53%.